2022
DOI: 10.1007/s11517-022-02649-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamic assessment of positive end-expiratory pressure in a tracheostomy tube connector during respiration

Abstract: High-flow oxygen therapy using a tracheostomy tube is a promising clinical approach to reduce the work of breathing in tracheostomized patients. Positive end-expiratory pressure (PEEP) is usually applied during oxygen inflow to improve oxygenation by preventing end-expiratory lung collapse. However, much is still unknown about the geometrical effects of PEEP, especially regarding tracheostomy tube connectors (or adapters). Quantifying the degree of end-expiratory pressure (EEP) that takes patient-specific spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Two types of resistance valves that matched the high-flow standard interface for exhalation were designed, thereby, further improving the high-flow respiratory humidification therapy device. Meanwhile, previous studies have shown that high-flow oxygen therapy was beneficial for increasing tidal volume and reducing respiratory frequency in COPD patients, thus reducing respiratory effort [ [19] , [20] , [21] ]. However, unlike AHRF, COPD patients themselves have the characteristic of obvious difficulty in exhalation.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of resistance valves that matched the high-flow standard interface for exhalation were designed, thereby, further improving the high-flow respiratory humidification therapy device. Meanwhile, previous studies have shown that high-flow oxygen therapy was beneficial for increasing tidal volume and reducing respiratory frequency in COPD patients, thus reducing respiratory effort [ [19] , [20] , [21] ]. However, unlike AHRF, COPD patients themselves have the characteristic of obvious difficulty in exhalation.…”
Section: Discussionmentioning
confidence: 99%